Social Justice in Sport and Exercise Psychology A Position Statement - Schinke, Robert 1966-; Habra, Bahaa; Kao, Sanfu; Lefebvre, Deborah; Middleton, Thierry; Petersen, Brennan (2019)
There are varied approaches that have been used in sport for development (SFD) projects. This article is focused on the move by sport and exercise psychology researchers toward community-based SFD projects where marginalized groups are centralized. The authors have chosen two of their projects to exemplify different approaches to SFD. An initial project with an Aboriginal community is critically examined to reveal cultural missteps that perpetuated cultural colonization-something antithetical to community capacity building. The second project is then considered because of its closer alignment with cultural praxis and community capacity building. This second project focuses on the initial developments of a YMCA physical activity project designed to meet the needs of forced immigrants (a self-titled name developed by the refugee community members) and the staff who work with them. We culminate with five postulates proposed for SFD project teams derived from our vantage in sport and exercise psychology, where community engagement and eventual self-governance are imperatives.
Keywords: Sport for development; community praxis; sport psychology